Evaluation of the antimicrobial activity of silver nanoparticles obtained by microwave-assisted green synthesis using Handroanthus impetiginosus (Mart. ex DC.) Mattos underbark extract - Tormena, Renata Pascoal Illanes (2020)
We describe here a green method for the preparation of silver nanoparticles (AgNPs), by a microwave-assisted synthesis route using Handroanthus impetiginosus underbark extract, with antibacterial activity. After optimizing the synthesis parameters with a Box–Benhken designed experiment, samples were characterized by powder XRD, TEM, UV-Vis spectroscopy, FTIR and zetametry. Using the overall optimized conditions of synthesis – time of reaction 15 min at 200 °C and plant extract/AgNO3 volume ratio equal to 10% – highly crystalline ∼13.4 nm-sized spherical AgNPs in a well-dispersed colloidal state were obtained. It was also proved that the plant extract compounds act as reductant and capping agents during synthesis to functionalize AgNPs, resulting in a negatively charged surface with high values of zeta potential in a wide range of pH, from acidic to alkaline media. Biological activity tests against Staphylococcus aureus and Escherichia coli and cell viability experiments showed that synthesized AgNPs were not toxic to HaCaT mammalian cells and presented a high efficiency against Gram-positive bacteria (S. aureus). This was associated with the synergistic combination of AgNP silver cores with the capping layer containing natural compounds with antimicrobial properties and considered an alternative to the AgNPs commonly obtained from conventional routes that present antibacterial effectiveness preferentially against Gram-negative strains.